Between “the local and the external”. The role of the local territory in the historical transformation of the food system in Metropolitan Lima - Pajuelo Bravo, Jose Alonso (2023)
The food system is a relevant component to sustain the cities, that arises from the interrelationship among stakeholders, infraestructures and natural resources, enabling food production, transformation, storage, distribution, commercialization and consumption, as well as food waste reuse. Thus, the system provides enough accessible and harmless food to the locals. In South America, the Pacific hydrographic region has hosted societies that created food systems that evolved from self-sufficient to open to economic chains. This has an impact on the management of production areas in the territory.  Since pre-Hispanic times, territory-adapted food systems were developed, which were focused on managing several production areas distributed in a group of basins. Nevertheless, the creation of large cities in this region, such as Metropolitan Lima, have resulted in the relocation of production areas out and away from their territory, which allows to differentiate what is local and what is external. Although the metropolis became a strong economic hub that contributes to the development of global and domestic economic chains; population growth and unplanned urbanization have caused soil degradation and the reduction of arable land (supplied to the real estate market), relegating the local metropolitan territory to food trade and consumption. In consequence, the food system is vulnerable to global or domestic crisis scenarios that could interrupt the external production process. This research analyzes the historical transformation of Lima’s food system to reflect on the local territory’s contribution to food security.